2020
DOI: 10.1038/s41563-020-0673-0
|View full text |Cite
|
Sign up to set email alerts
|

Engineering high-energy-density sodium battery anodes for improved cycling with superconcentrated ionic-liquid electrolytes

Abstract: Non-uniform metal deposition and dendrite formation in high density energy storage devices reduces the efficiency, safety, and life of batteries with metal anodes. Superconcentrated ionic liquid (IL) electrolytes (e.g. 1:1 IL:alkali ion) coupled with anode preconditioning at more negative potentials can completely mitigate these issues, and therefore revolutionize high density energy storage devices. However, the mechanisms by which very high salt concentration and preconditioning potential enable uniform meta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
259
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 204 publications
(272 citation statements)
references
References 53 publications
13
259
0
Order By: Relevance
“…Recently, Rakov et al. [ 59 ] reported that superconcentrated ionic‐liquid electrolytes, such as 1:1 N ‐methyl‐N‐propylpyrrolidinium bis(fluorosulfonyl)imide (C3mpyr‐FSI): sodium bis(fluorosulfonyl) imide (NaFSI), coupled with anode preconditioning at more negative potentials could completely mitigate dendrite formation. Sun et al.…”
Section: Liquid Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Rakov et al. [ 59 ] reported that superconcentrated ionic‐liquid electrolytes, such as 1:1 N ‐methyl‐N‐propylpyrrolidinium bis(fluorosulfonyl)imide (C3mpyr‐FSI): sodium bis(fluorosulfonyl) imide (NaFSI), coupled with anode preconditioning at more negative potentials could completely mitigate dendrite formation. Sun et al.…”
Section: Liquid Electrolytesmentioning
confidence: 99%
“…X-ray scattering revealed that Li + −O(FSI − ) atom−atom correlation has an average distance of about 1.94 Å, which is evidently longer than that of the Li + −O(TFSI − ) (1.86 Å). Recently, Rakov et al [59] reported that superconcentrated ionic-liquid electrolytes, such as 1:1 N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)imide (C3mpyr-FSI): sodium bis(fluorosulfonyl) imide (NaFSI), coupled with anode preconditioning at more negative potentials could completely mitigate dendrite formation. Sun et al [60] found that 5 m LiFSI in EMim-FSI with 0.1 m NaTFSI as key additive can form hybrid passivation interphases and avoid lithium plating.…”
Section: Ionic Liquidsmentioning
confidence: 99%
“…Lately, the role of the electrolyte structure at the anode in improving the stability of the SEI layer and Na deposition was revealed. [ 133 ] Figure 7h shows a distinct effect on the interfacial structure from NaFSI concentration through AFM force measurement and molecular dynamics (MD). A highly aggregated Na x (FSI) y structure in the form of molten salt was found in the innermost electrolyte layers, especially on the negatively charged surface.…”
Section: Stabilization Of the Sei On Na Metal Anodesmentioning
confidence: 99%
“…h) Interfacial layering nanostructure comparation for C 3 mpyrFSI IL with different NaFSI salt concentrations (h 1 :0 mol%; h 2 :10 mol%; h 3 :50 mol%) by AFM and MD. Reproduced with permission [133]. Copyright 2020, Nature Publishing Group.…”
mentioning
confidence: 99%
“…Therefore, several methods have been developed and optimized such as the introduction of small molecule plasticizers, e.g., ionic liquids (ILs), [ 5 ] carbonates, [ 6 ] or ethers, [ 7 ] to polymer‐salt developed gel polymer electrolytes (GPEs) in the quasi‐solid‐state. [ 8 ] The solid polymer hosts provide robust mechanical strength and binding to liquid electrolytes, avoiding the safety risks caused by leakage, while the Li + transport proceeds mainly along the liquid track distributed in the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%